Farm Stores in agriburbia: The roles of agricultural retail on the rural-urban fringe - Lenore Newman; Lisa Jordan Powell; Jennifer Nickel; Dylan Anderson; Lea Jovanovic; Eileen Mendez; Barbara Mitchell; Kathryn Kelly-Freiberg (Canadian Food Studies, 2017)
This investigation highlights the role of on-farm stores on the rural/urban fringe near Vancouver, Canada. Operators achieve higher economic return by targeting populations interested in local food and in agritourism, including customers from towns in the fringe and from the larger nearby urban center. The farm stores catered to a rural idyll that reflects cultural conceptions of farm life. We suggest the multifunctional landscape of the farm store provides economic and cultural benefits, and should be considered as sustaining agriculture. The study revealed that farm store operators in particular share the rural idyll of urban consumers, though agritourism operators are more consciously including rural elements in their operations.